Pengaruh Cashless Payment, Literasi Keuangan dan Media Sosial terhadap Perilaku Konsumtif Generasi Z di Kota Cirebon - Delina; Syaeful Bakhri; Edy Setyawan (Journal of Sharia, Law, and Economics, 2026)
Advances in digital technology have driven the growing use of cashless payments, which offer convenience and efficiency in transactions. However, this convenience also has the potential to shift consumption patterns toward greater spending. This situation becomes increasingly problematic when the high use of cashless payments is not balanced by adequate financial literacy, leaving individuals less able to control their spending. Additionally, the high use of social media, with its various promotions, trends, and consumerist lifestyles, is also suspected of reinforcing the drive toward consumption. This phenomenon indicates a relationship between cashless payments, financial literacy, and social media that warrants further research, particularly among Generation Z in the city of Cirebon.   This study aims to examine the influence of cashless payments, financial literacy, and social media on consumer behavior. The study employs a quantitative approach using primary data collected through questionnaires, interviews, and literature review. The study population consists of Generation Z in Cirebon City who use cashless payments in their daily consumption activities. The research sample consisted of 100 respondents selected using non-probability sampling with a purposive sampling method. Data analysis was conducted through tests of validity, reliability, normality, linearity, multicollinearity, and heteroscedasticity, as well as multiple linear regression and hypothesis testing.   The results of the study indicate that cashless payments and social media have a positive and significant effect on consumer behavior, while financial literacy has a negative and significant effect. Collectively, these three variables have a significant effect on the consumer behavior of Generation Z in Cirebon City.